Stigmate politique et usages de la ressource publique : le gecekondu comme espace de mobilisation - Marie Le Ray (European Journal of Turkish Studies)
This monographic inquiry describes and analyses the forms of commitment of different associations in the gecekondu as an over-controlled public space. Mustafa Kemal Mahallesi is an Istanbul neighbourhood known for its political history and stigmatised as a stronghold of some illegal far-leftist groups. Taking this case study, we first examine the ways stigma hinders and constrains physical and discursive investments of the public space. This contribution goes on interrogating the ability of public local actors to go beyond and create themselves some ‘protected’ areas where discussion, possibly resistance, would still be possible. It seems that behind a formal obedience to the official grammar of public life, local actors get their voice back and regain the right of saying what the neighbourhood and its symbolic identity should be. Finally, scaling down, the paper explores local uses of some ‘in-between public and private’ spaces like everyday interactions around tea or cards, mourning and funerals, folklore lessons or communitarian commemorations. In a space under constraints, these are privileged places where identities and loyalties are built and rebuilt, and through which public space may also eventually be enlarged.